Effect of Zinc Oxide Modification by Indium Oxide on Microstructure, Adsorbed Surface Species, and Sensitivity to CO - Marikutsa, Artem; Rumyantseva, Marina; Gaskov, Alexander; Batuk, Maria; Hadermann, Joke; Sarmadian, Nasrin; Saniz, Rolando; Partoens, Bart; Lamoen, Dirk (Frontiers in Materials, 2019)
Additives in semiconductor metal oxides are commonly used to improve sensing behavior of gas sensors. Due to complicated effects of additives on the materials microstructure, adsorption sites and reactivity to target gases the sensing mechanism with modified metal oxides is a matter of thorough research. Herein, we establish the promoting effect of nanocrystalline zinc oxide modification by 1 – 7 at.% of indium on the sensitivity to CO gas due to improved nanostructure dispersion and concentration of active sites. The sensing materials were synthesized via an aqueous coprecipitation route. Materials composition, particle size and BET area were evaluated using X-ray diffraction, nitrogen adsorption isotherms, high-resolution electron microscopy techniques and EDX-mapping. Surface species of chemisorbed oxygen, OH-groups and acid sites were characterized by probe molecule techniques and infrared spectroscopy. Zinc oxide particle size was found to decrease and the BET area to increase with the amount of indium. The additive was observed in the form of amorphous indium oxide segregated on agglomerated crystalline ZnO nanoparticles. The concentration of surface species was found to be higher on In-modified zinc oxide. With the increase of indium content, the sensor response of ZnO(In) to CO was improved. Using in situ infrared spectroscopy, it was shown that oxidation of CO molecules was enhanced on the modified zinc oxide surface. The effect of modifier was attributed to promotion of surface OH-groups and enhancement of CO oxidation on the segregated indium ions, as suggested by DFT in previous work.